2006
DOI: 10.1128/jb.00441-06
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and Structural Characterization of the Secreted Chorismate Mutase (Rv1885c) from Mycobacterium tuberculosis H 37 R v : an *AroQ Enzyme Not Regulated by the Aromatic Amino Acids

Abstract: The protein has an all alpha-helical structure, and the active site is formed within a single chain without any contribution from the second chain in the dimer. Analysis of the structure shows a novel fold topology for the protein with a topologically rearranged helix containing Arg 134 . We provide evidence by site-directed mutagenesis that the residues Arg 49 , Lys 60 , Arg 72 , Thr 105 , Glu 109 , and Arg 134 constitute the catalytic site; the numbering of the residues includes the signal sequence. Our inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 57 publications
1
44
0
Order By: Relevance
“…The ScCM of S. cerevisiae and AnCM of Aspergillus nidulans are inhibited by Tyr and Phe and are stimulated by Trp (Krappmann et al, 1999;Schmidheini et al, 1989). Similar to MtbCM (Kim et al, 2006), CM0819 in C. glutamicum is not subject to any regulation by aromatic amino acids. But CM0819 together with chorismate and prephenate regulates DS2098 activity via allosteric inhibition, similar to what was observed for the bifunctional CM from B. subtilis (Jensen & Nester, 1965).…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…The ScCM of S. cerevisiae and AnCM of Aspergillus nidulans are inhibited by Tyr and Phe and are stimulated by Trp (Krappmann et al, 1999;Schmidheini et al, 1989). Similar to MtbCM (Kim et al, 2006), CM0819 in C. glutamicum is not subject to any regulation by aromatic amino acids. But CM0819 together with chorismate and prephenate regulates DS2098 activity via allosteric inhibition, similar to what was observed for the bifunctional CM from B. subtilis (Jensen & Nester, 1965).…”
Section: Discussionmentioning
confidence: 77%
“…There was no observable feedback regulation of CM activity at concentrations of 0.01-10 mM of any of Phe, Trp or Tyr. This is similar to MtbCM from Mycobacterium tuberculosis, which was not subject to feedback regulation by Phe, Trp or Tyr (Kim et al, 2006).…”
Section: Cm0819 Activity Is Not Regulated By Phe Tyr and Trp But Ismentioning
confidence: 78%
“…These enzymes consist of three constitutively expressed subtypes: a monofunctional form (Berlyn and Giles, 1969;Chaudhuri et al, 1987), a bifunctional form found in plants and a multifunctional form of dehydroquinase, which is a large polypeptide (Kleanthous et al, 1990). Kim et al (2006) reported the presence in Mycobacterium tuberculosis of such enzymes which are essential for the biosynthesis of phenylalanine, tyrosine, tryptophan (Garbe et al, 1991), and other aromatic compounds in bacteria and other organisms such as fungi, algae and plants, but they are absent in mammals (Haslam, 1993;Kim et al, 2006). An advantage of the non-occurrence of these enzymes in mammals is the possibility of the development of new drugs (Cole et al, 1998;Camus et al, 2002;Kim et al, 2006).…”
Section: Arob and Aroq: Amino Acid Biosynthesismentioning
confidence: 99%
“…We show in the present study that these are both monofunctional CMs of the AroQ class. It should be pointed out that Rv1885c has been recently characterized in detail by others (27,41,45). We also show that homologues of each CM from M. tuberculosis are found in Mycobacterium smegmatis, a nonpathogenic species.…”
Section: Tuberculosis (Tb) a Serious Infectious Disease Caused Bymentioning
confidence: 76%